Law and Justice in Timor-Leste: Challenges and Prospects - Reinaldo Francisco Luis (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2025)
The legal and judicial system in Timor-Leste continues to face various structural and substantive challenges that hinder access to justice, particularly for communities in remote areas. The lack of judicial infrastructure, limited human resources, and the imbalance between customary legal mechanisms and the formal legal system are key factors that complicate the effective and equitable enforcement of the law. In the context of protecting vulnerable groups, such as women and children, the existing legal system has yet to fully provide optimal protection as mandated by the Constituição da República Democrática de Timor-Leste and other relevant legislation. This study aims to critically analyze the barriers and challenges to accessing justice in Timor-Leste and to evaluate the prospects for legal reform to enhance the effectiveness of the judicial system. Employing legal research methods and an empirical approach, this study examines the existing legal framework and its practical implementation through case studies and secondary data analysis. The findings reveal that the limited number of courts, the shortage of competent judges and prosecutors, and the unequal distribution of legal aid services constitute major obstacles within Timor-Leste’s judicial system. Furthermore, customary law—often the primary recourse for many communities—frequently conflicts with human rights principles, particularly regarding the protection of women and children. Legal reforms, including investments in judicial infrastructure, capacity building for law enforcement officials, and the harmonization of customary and formal legal systems, are essential to improving access to justice.